Congenital pleuroperitoneal hernia presenting as gastrothorax in five cavalier King Charles spaniel dogs. (30th April 2018) - Rossanese, M.; Pivetta, M.; Pereira, N.; Burrow, R.
Abstract : Five cavalier King Charles spaniels were examined for acute onset of respiratory distress. Thoracic radiographs demonstrated diaphragmatic hernia and tension gastrothorax, visible as a distended stomach occupying the left caudal thoracic cavity. Exploratory midline coeliotomy confirmed congenital pleuroperitoneal diaphragmatic hernia with herniation and dilatation of the stomach. The hernia configuration was consistent in all cases, with a defect affecting the left diaphragmatic crus. Congenital pleuroperitoneal diaphragmatic hernia is a rare condition caused by a defect in the dorsolateral diaphragm. Defects of the left crus of the diaphragm could result in the herniation of the stomach into the thoracic cavity with possible subsequent tension gastrothorax. Cavalier King Charles spaniels may have a predisposition to this condition. Tension gastrothorax is an acute life‐threatening consequence of gastric herniation through a diaphragmatic defect that must be promptly recognised and surgically treated.